Experience in the Management of Pancreatic Adenocarcinoma with Whipple Procedure at the Institute of Social Security and Services for State Workers of Puebla - González, Cristian Jair Flores; Blanco, Miguel Ángel Alonso; Flores, Edgar Grageda; Bernal, Carlos Alberto López; Bernal, Norma Rojas; Rodriguez, Georgina Loyola; Gonzalez, Jorge Rojas; Molina, Mónica Patricia Hernández; Durango Hernandez, Diomedes Jesus (British Journal of Healthcare and Medical Research, 2025)
Background: Currently, in the management of periampullary tumors, pancreatic carcinoma is the most frequent, considered a tumor with a poor prognosis. Approximately 95% of cases are exocrine cell tumors, most commonly pancreatic ductal adenocarcinomas (PDAC). According to INEGI, in Mexico, PDAC is the twelfth leading cause of cancer, with 4,489 cases diagnosed annually, accounting for 4.9% of oncological deaths. Methods: A retrospective descriptive observational study was designed for patients managed with pancreaticoduodenectomy during 2023 and 2024, at a tertiary care center in Puebla, Mexico. Results: A total of 16 patients went to surgery, with malignancy reported in 13 of them. A predominance of female-to-male ratio greater than 2:1 was observed, and the complication rate was 81%, with respiratory complications predominating, followed by biliopancreatic fistula. Conclusions: The Whipple procedure is considered a high-complexity surgery with a high risk of complications. However, in selected cases, it is the treatment of choice for periampullary tumors, showing better survival, especially in the early stages of pancreatic cancer.